A rozsnyói egyházmegye tanítóinak és papjainak 1938-as petíciója - Bartók, Béla (Közép-Európai Közlemények, 2010)
The First Vienna Awards in 1938 was not only a political challenge but also a cultural challenge for the Hungarian minority of the former Czechoslovakia. The Hungarian language education had got a chance to progress free after twenty years of the disadventage. We tried to make a reconstruction on the momentary state of the Hungarian catholic elementary schools with help of a source that was made in 1939 in the centre of the Dioecese of Roznava. It took a short overview about the former gravamens of the minority schools and the Catholic Church, on the conflicts of the change of the state power. The priests and the masters of the archdeaconry of Torna wrote their requests and sent their petition to the Ministry of Religion and Education. The requests concerned to the social conditions of the priests and the masters, who lived between difficult circumstances in the first Republic of Czechoslovakia. before the recapture. This snapshot shows the privity of the rural intelligence and origins and characteristics of their nationalist and clerical ideology.